A institucionalização da agricultura familiar no mercosul - Costa, Júlia Jacomini [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The Mercosul project, signed in 1991, represents the union of a political project, characterized by a democratic agreement among its members, with an economical project characterized by the trade liberalization among its regional members and among these with the global economy. So, it was constituted, with the aim to expand the national trades by the integration, to increase the economic development process with social justice. However, the Mercosul follows the historical trajectory of Latin America integration, characterized by models that aimed the economical development from the strengthening of the industry. According to that, the Mercosul politics are priority for economic issues, focused in the industrialization and trade relations, giving less priority to the social demands. In opposition to such ideas, in 2004 was created the Especialized Meeting about Family Farm (Reunião Especializada sobre Agricultura Familiar - REAF) in the Mercosul, that aim to strengthen the public policies of the sector, to promote the commercialization of the family farm products in the region. So, the family farm, a sector historically marginalized from the integration projects, it is institutionalized in the Mercosul. In that way, the aim of this research is to discuss the reasons that leaded to the family farm institutionalization, and also to analyze the advances and problems of the Especialized Meeting about Family Farm

O projeto do Mercosul, assinado em 1991, representa a união de um projeto político, marcado pelo compromisso democrático entre os seus membros, com um projeto econômico, pautado na liberalização e na abertura comercial entre os membros regionais e entre estes com a economia global. O Mercosul foi constituído, dessa forma, com o objetivo de ampliar os mercados nacionais através da integração, para a aceleração do processo de desenvolvimento econômico com justiça social. No entanto, o Mercosul acompanha a trajetória histórica de integração na América Latina, marcada por modelos que buscavam o desenvolvimento econômico a partir do fortalecimento do setor industrial. Nesse sentido, suas políticas são prioritariamente destinadas às questões econômicas, voltadas principalmente à industrialização e às relações comerciais, deixando em segundo plano as demandas sociais. À contramão destas idéias, em 2004 foi criada a Reunião Especializada sobre Agricultura Familiar (REAF) no Mercosul, com o objetivo de fortalecer as políticas públicas para o setor, promover o comércio dos produtos da agricultura familiar e facilitar a comercialização de produtos oriundos da agricultura familiar na região. Assim, a agricultura familiar, um setor historicamente marginalizado pelos projetos de integração, é institucionalizada na esfera do Mercosul. Nesse sentido, o objetivo deste trabalho é discutir as razões que levaram à sua institucionalização, assim como analisar os avanços e os entraves da Reunião Especializada sobre Agricultura Familiar
Keywords: MERCOSUL; Reunião Especializada sobre Agricultura Familiar; REAF; Agricultura familiar; Desenvolvimento economico - Aspectos sociais; Desenvolvimento rural; Agricultura; Politicas publicas; Geografia agrícola; Family farms; Economic development - Social aspects; Rural development; Agriculture; Public policy; Agricultural geography